Desempenho mecânico e durabilidade de um solo argiloso melhorado com resíduo do polimento de vidro, cimento e cloreto de sódio para uso em base e sub-base de pavimentos - Ordoñez Muñoz, Yeimy (2025)
The growing demand for sustainable solutions in civil engineering has driven research on reusing waste materials as an alternative in developing geotechnical materials. Despite advances in the field, few studies have addressed the use of waste in local soils, such as the red soil from the Guabirotuba Formation, which is common in Curitiba and surrounding areas but remains understudied. Furthermore, the lack of studies combining glass powder waste (GPW), cement, and sodium chloride (NaCl) as an alkali activator highlights a state-of-the-art gap. This study assessed the feasibility of using glass powder waste (GPW) (5%, 15%, and 25%), cement (2%, 5%, and 8%), and NaCl as soil improvement agents for Guabirotuba Formation soil, targeting their application in pavement base and subbase layers. A series of laboratory tests was carried out to assess the influence of variables including cement, GPW, and NaCl contents, porosity (η), curing time, and compaction energy on unconfined compressive strength (qu), splitting tensile tensile strength (qt), and durability based on accumulated mass of loss (AML). The best-performing blends regarding elastic deformation (MR), plastic deformation (PD), and mineralogical and microstructural properties were analyzed. The MEDINA methodology was applied to evaluate the potential use of these materials as base and subbase layers in road pavements for primary collector systems (PCS) and principal arterial systems (PAS). The results indicated that adding up to 15% GPW and 1% NaCl led to the formation of alkali-activated materials, allowing a 3% reduction in the amount of cement required to achieve the target strength, which previously demanded a higher cement content. The AML of the untreated soil (100%) was reduced to below 7% in the studied blends. Relationships among porosity, volumetric cement content (η/Civ), and binder content (η/Biv) enabled the development of equations to predict qu, qt, and durability. The MR varied with the stress state: in untreated soil, it increased with confining stress and decreased with increasing deviatoric stress, ranging from 310 to 297 MPa. For the blends, MR increased with both stress components, varying from 261 to 1003 MPa. Blends containing cementGPW-NaCl exhibited the highest MR values and the lowest PD. The PD of the evaluated materials was considered acceptable, as it did not exceed 6% of the typical track of wheel sinking established in the literature for pavement layers. Furthermore, all materials tended to plastic accommodation (Shakedown). Simulations using the MEDINA methodology indicated that, in the PCS, the untreated soil used as base and subbase layers was sufficient to meet the criteria for cracked area and PD established by the standards. However, for PAS under N=107 load repetitions, adding 5% cement, 15% GPW, and 1% NaCl was necessary to meet these performance requirements. The mineralogical and microstructural results evidenced the formation of alkaliactivated gels in the form of calcium and sodium aluminosilicate hydrate (C,N)-A-S-H, as indicated by the Ca/Si, Al/Si, and Na/Si ratios. These new materials exhibited improved mechanical properties, contributing to the sustainable use of waste in civil construction and opening new possibilities for the use of local soils in pavement applications.